PELAKSANAAN JUAL BELI TANAH YANG BELUM BERSERTIFIKAT DI KECAMATAN BLANGPEGAYON KABUPATEN GAYO LUES - Hanisa, Hanisa; Sulaiman, Sulaiman; Yulia, Yulia (Fakultas Hukum Universitas Malikussaleh, 2024)
This study aims to research the implementation of buying and selling land that has not been certified and to find out information and understand the legal results of buying and selling land that has not been certified in Blangpegayon District, Gayo Lues Regency. This research is empirical juridical research using a law and case approach that obtains data through field research and literature. Based on the results of the research, it is known that in the implementation of buying and selling for land that has not been certified in Blangpegayon District, Gayo Lues Regency, it was found that there was still a lot of buying and selling for land that had not been certified, according to the people of Blangpegayon District, Gayo Lues Regency, that buying and selling was underhand for land that had not been certified and only It is felt that using a receipt is sufficient because processing the certificate requires expensive costs and a more complicated process. The legal consequences of buying and selling underhand for land that has not been certified in Blangpegayon District, Gayo Lues Regency are still valid but the legality is not yet valid because there is no certificate so it can lead to settlements at a later date.